2019
DOI: 10.1139/cjb-2018-0195
|View full text |Cite
|
Sign up to set email alerts
|

Inuit plant use in the eastern Subarctic: comparative ethnobotany in Kangiqsualujjuaq, Nunavik, and in Nain, Nunatsiavut

Abstract: Plants are important in traditional Inuit life. They are used for food, tea, medicine, etc. Based on semi-structured interviews with 35 informants, we documented and compared plant names and uses in Kangiqsualujjuaq, Nunavik, and in Nain, Nunatsiavut. Plant names and uses were expected to be similar between communities owing to common boreal–subarctic environments and cultural ties. Both communities reported the same number of taxa, with equivalent proportions of vascular and nonvascular plants, growth forms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Multiple recent studies have demonstrated local human impacts on subarctic forests in Labrador (northeastern Canada) including through the direct harvesting of wood (Roy et al 2012(Roy et al , 2017Lemus-Lauzon et al 2016 and through cultural land and fire management (Lemus-Lauzon et al 2012;Oberndorfer et al 2017;Cuerrier et al 2019). As pointed out by these authors, studies of the ecological history of northern forests and of their management frequently underestimate or ignore the scale of anthropogenic forest impacts in regions with histories of minimal commercial or industrial forestry activity.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple recent studies have demonstrated local human impacts on subarctic forests in Labrador (northeastern Canada) including through the direct harvesting of wood (Roy et al 2012(Roy et al , 2017Lemus-Lauzon et al 2016 and through cultural land and fire management (Lemus-Lauzon et al 2012;Oberndorfer et al 2017;Cuerrier et al 2019). As pointed out by these authors, studies of the ecological history of northern forests and of their management frequently underestimate or ignore the scale of anthropogenic forest impacts in regions with histories of minimal commercial or industrial forestry activity.…”
Section: Introductionmentioning
confidence: 99%
“…Although native foods are certainly still a marker of indigenous identity in Chukotka (Yamin-Pasternak 2014), just as they are among other arctic cultures (Cuerrier et al 2019;Jones 2010), that does not mean these customs are static. Some, like the "mouse roots" we discuss here, appear to be declining, while others, such as mushrooms (Yamin-Pasternak 2007), have been added as a significant part of traditional subsistence.…”
Section: Resultsmentioning
confidence: 99%
“…The many uses of this plant have been well documented in numerous publications (Alm 2004, Cuerrier & Ampong-Nyarko 2014. This plant has had a history of traditional use as both food and medicine among the Inuit (Cuerrier & Hermanutz 2012, Cuerrier et al 2019, Mardones 2019. Recently community members expressed interest in developing a sustainable enterprise based upon cultivation of Rhodiola native to coastal Labrador's Inuit lands of Nunatsiavut (Newfoundland and Labrador, Canada) utilizing biocultural design concepts (Davidson-Hunt et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a scarcity of ethnobotanical research from the Eastern Canadian Arctic (Davis & Banack 2012, Meis Mason et al 2012, specifically with Nunatsiavut Inuit of Labrador. At the time of this study, no ethnobotanical work had been done in the town of Rigolet (Cuerrier & Hermanutz 2012, Cuerrier et al 2019Downing & Cuerrier 2011;Karst & Turner 2011). Among Nunatsiavut Inuit, referred to as Nunatsiavummiut, connection to the land is foundational to traditional knowledge and cultural identity (Cuerrier et al 2012a, Downing & Cuerrier 2011.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation